Myb-Related Schizosaccharomyces pombe cdc5p Is Structurally and Functionally Conserved in Eukaryotes - Ohi, Ryoma (American Society for Microbiology, 1998)
Schizosaccharomyces pombe cdc5p is a Myb-related protein that is essential for G(2)/M progression. To explore the structural and functional conservation of Cdc5 throughout evolution, we isolated Cdc5-related genes and cDNAs from Saccharomyces cerevisiae, Caenorhabditis elegans, Drosophila melanogaster, and Homo sapiens. Supporting the notion that these Cdc5 gene family members are functionally homologous to S. pombe cdc5(+), human and fly Cdc5 cDNAs are capable of complementing the temperature-sensitive lethality of the S. pombe cdc5-120 mutant. Furthermore, S. cerevisiae CEF1 (S. cerevisiae homolog of cdc5(+)), like S. pombe cdc5(+), is essential during G(2)/M. The location of the cdc5-120 mutation, as well as mutational analyses of Cef1p, indicate that the Myb repeats of cdc5p and Cef1p are important for their function in vivo. However, we found that unlike in c-Myb, single residue substitutions of glycines for hydrophobic residues within the Myb repeats of Cef1p, which are essential for maintaining structure of the Myb domain, did not impair Cef1p function in vivo. Rather, multiple W-to-G substitutions were required to inactivate Cef1p, and many of the substitution mutants were found to confer temperature sensitivity. Although it is possible that Cef1p acts as a transcriptional activator, we have demonstrated that Cef1p is not involved in transcriptional activation of a class of G(2)/M-regulated genes typified by SWI5. Collectively, these results suggest that Cdc5 family members participate in a novel pathway to regulate G(2)/M progression.